2009
DOI: 10.1093/brain/awp144
|View full text |Cite
|
Sign up to set email alerts
|

CCR2+Ly-6Chi monocytes are crucial for the effector phase of autoimmunity in the central nervous system

Abstract: The chemokine receptor CCR2 plays a vital role for the induction of autoimmunity in the central nervous system. However, it remains unclear how the pathogenic response is mediated by CCR2-bearing cells. By combining bone marrow chimerism with gene targeting we detected a mild disease-modulating role of CCR2 during experimental autoimmune encephalomyelitis, a model for central nervous system autoimmunity, on radio-resistant cells that was independent from targeted CCR2 expression on endothelia. Interestingly, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
360
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 400 publications
(377 citation statements)
references
References 49 publications
15
360
1
1
Order By: Relevance
“…The pathogenic monocyte response in Tgfbr2 −/− OT-II RIP-mOva mice is in part dependent on GM-CSF, a cytokine with established roles in myeloid cell homeostasis and monocyte activation (40)(41)(42)(43). GM-CSF also promotes the development of autoimmune diseases such as arthritis and EAE (45,46,59,60), both of which are associated with pathogenic myeloid cell responses (36,37,61). Indeed, GM-CSF signaling has been demonstrated to trigger an inflammatory signature in monocytes that contributes to their pathogenic function in autoimmunity (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic monocyte response in Tgfbr2 −/− OT-II RIP-mOva mice is in part dependent on GM-CSF, a cytokine with established roles in myeloid cell homeostasis and monocyte activation (40)(41)(42)(43). GM-CSF also promotes the development of autoimmune diseases such as arthritis and EAE (45,46,59,60), both of which are associated with pathogenic myeloid cell responses (36,37,61). Indeed, GM-CSF signaling has been demonstrated to trigger an inflammatory signature in monocytes that contributes to their pathogenic function in autoimmunity (62).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas inflammatory monocytes are wellknown innate immune cells mobilized during infection for host defense responses (35), recent studies have revealed that inflammatory monocytes are also essential for the induction of tissue damage in immunization models of autoimmune diseases such as experimental autoimmune encephalitis (EAE) (36,37). Although T cells play an essential role in the immunization models of autoimmunity, the potential for directly activating monocytes by adjuvant-mediated triggering of pattern-recognition receptors remains.…”
Section: Pathogenic Role Of Inflammatory Monocytes In Diabetes Triggementioning
confidence: 99%
“…In this regard, CCR2 has been shown to affect EAE pathogenesis based on observations that CCR2 −/− mice were resistant to EAE, although this effect was dependent on the genetic background of the mice (34)(35)(36). Recent studies have unraveled the mechanism of disease resistance in CCR2 −/− animals by demonstrating a disease-promoting role of CCR2 + Ly-6C high monocytes during induction of EAE (37). During the preparation of this manuscript, it was further suggested that a reduction in the numbers of (TNF-producing) inflammatory macrophages observed in CNS, spleen, and LN were causative for enhanced EAE resistance in CCR4 −/− mice (38).…”
Section: Discussionmentioning
confidence: 99%
“…During some insults to the brain, circulating monocytes can be mobilized to breach the BBB, migrate into the brain, and subsequently contribute to the neuroimmune response in association with microglia (11,12). Peripheral monocytes are known to enter the brain after traumatic brain injury and contribute to neuronal injury (13), and they play a similar role in multiple sclerosis mouse models (14,15).…”
mentioning
confidence: 99%